Queering spectatorship in K-pop: The androgynous male dancing body and western female fandom. (1st March 2015) - Oh, Chuyun
Employing performance studies and queer studies, this article explores the subversive nature of western female fandom's consumption of male dancing bodies in Korean pop (K-pop) culture. By offering close readings of fan-made compilation videos and analysing fans' comments on YouTube, this article analyses how K-pop male idols' androgynous gender fluidity provides a space for queering female desire against normative white masculinity. Through video editing, fans 'choreograph' their desire by fetishizing K-pop male dancers' specific body parts and movements and transform themselves from displayed objects to subjects of the gaze. Moreover, through active engagement online, fans transcend their status from spectators to performers who actively enact alternative sexualities and gender roles in a public space. K-pop male singers' gender performativity is significant, as it challenges rigid gender binaries in western culture – homosexuality/heterosexuality, masculine/feminine body and behaviour, and masculinized gaze/feminized object – as embodiments of hybridized male femininity, which this article calls liminal masculinity.